Efficient interest‐aware data dissemination in mobile opportunistic networks. (1st October 2019) - Yu, Sui; Zhang, Lichen; Li, Peng; Li, Lixia; Yan, Bin; Cai, Zhipeng
Summary: In mobile opportunistic networks, the high mobility of humans and the resource limitation of smart mobile devices pose a great challenge to the design of efficient data dissemination, in which data packets generated from publishers need to be delivered to the subscribers via opportunistic encounters. The current data dissemination schemes generally concentrate on the similarity among nodes while ignoring the similarity between nodes and data packets, which leads to that data packets move back and forth among the nodes with similar social features instead of reaching to the subscribers efficiently. In this paper, an efficient interest‐aware data dissemination approach is proposed in mobile opportunistic networks, in which the similarity between nodes and data packets is used to determine whether a node is a potential destination. Moreover, both the social feature and the residual energy are considered to choose an appropriate relay node, and then determine the number of packet's replicas. The simulation results show that efficient interest‐aware data dissemination provides high efficiency and less transmission overheads compared with the traditional approaches.